POSSIBLE ANTHROPOMETRIC EXPLANATION OF AGE-RELATED CHANGES IN SPLENIC VOLUME IN A SAMPLE OF HEALTHY IRAQI INDIVIDUALS USING ULTRASONOGRAPHY (Iraqi Journal of Medical Sciences, 2016)
Background:Spleen is a hemopoietic organ which is capable of supporting elements of different systems. Determination of spleen size is important in diagnosing small, normal or enlarged spleens. Songraphy can rapidly and reliably help to determine the size of the spleen.Objective:The purpose of this study was to analyze the changes in splenic volume with respect to age using anthropometric measurents (body mass index (BMI), body surface area (BSA)) and to find the predicting equation of spleen volume.Methods: 215 Iraqi subjects (103 females with age range (6-74) years and 112 males with age range (7-75) years) without conditions that can affect the spleen or splenic abnormalities were evaluated with ultrasonography. Spleen length, width and thickness were measured and spleen volume was calculated. Spleen size was correlated with age, gender, BMI and BSA.Results:The mean splenic volume was significantly variable in different age groups.The spleen volume increases starting from childhood to reach a peak in a young adults (20-49) years and then declines in the middle age and elderly subjects (age with greater than 50 years). Splenic volume for males was significantly higher than females. BSA had a stronger linear correlation with splenic volume than BMI. Multiple regression analysis indicated that BSA had significant positive association with spleen volume in subjects younger than 50 years.Conclusion:Spleen volume was significantly variable among different age groups. Spleen volume affected by BSA especially in subjects younger than 50 years. These results illustrate that the normal value of spleen volume affected by different factors 1) age 2) sex 3) BMI 4) BSA.Key words:Spleen volume, Ultrasonography, Age, BMI, BSA
Keywords: Spleen volume; Ultrasonography; Age; BMI; BSA